2006
DOI: 10.1111/j.1365-2761.2006.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunological parameters in farmed gilthead sea bream, Sparus aurata L., before and during outbreaks of ‘winter syndrome’

Abstract: In recent years, 'winter syndrome' has caused severe economic losses in many marine farms in southern Europe. This study compared the activity of the immune system in healthy, asymptomatic and diseased gilthead sea bream. Serum protein and immunoglobulin content were evaluated as well as serum complement activity from these groups of fish. Differential leucocyte counts were also determined. Immunological assays were performed to determine intra- and extracellular 'respiratory burst' activity as non-specific im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…A slight abdominal distension, pallor of the gills and corneal opacity may also be noticed. The main lesions observed in necropsy are a pale and friable liver, sometimes haemorrhagic, and a distended gut tract filled with a clear fluid, with a whitish mucous content in the lumen (Bovo et al 1995;Padrós et al 1998;Tort et al 1998b;Contessi et al 2000Contessi et al , 2006Gallardo et al 2003). The main histopathological findings are observed in the liver, pancreas, muscle, intestine and, in some cases, also in the kidney.…”
Section: Pathology and Histological And Biochemical Profilesmentioning
confidence: 92%
See 2 more Smart Citations
“…A slight abdominal distension, pallor of the gills and corneal opacity may also be noticed. The main lesions observed in necropsy are a pale and friable liver, sometimes haemorrhagic, and a distended gut tract filled with a clear fluid, with a whitish mucous content in the lumen (Bovo et al 1995;Padrós et al 1998;Tort et al 1998b;Contessi et al 2000Contessi et al , 2006Gallardo et al 2003). The main histopathological findings are observed in the liver, pancreas, muscle, intestine and, in some cases, also in the kidney.…”
Section: Pathology and Histological And Biochemical Profilesmentioning
confidence: 92%
“…Hepatic changes may vary from incipient steatosis (Contessi et al 2006) to severe fatty degeneration in hepatocytes (Galeotti et al 1999;Padrós et al 1998;Tort et al 1998b;Contessi et al 2000). Atrophy and degeneration of the exocrine pancreatic tissue within the liver or in the perivisceral tissue is also usually reported, and granulocyte infiltration of the pancreatic tissue has been observed (Contessi et al 2006). Granular degeneration and necrosis in white muscle fibres is another very common finding.…”
Section: Pathology and Histological And Biochemical Profilesmentioning
confidence: 97%
See 1 more Smart Citation
“…In some outbreaks, mortality rates reached as high as 30-50% and it caused severe economic losses 2,10 . In this study, during the outbreak, approximately two million dead fish were found and it was resulted from serious economic losses in all affected farms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that WD outbreaks are appeared during the winter seasons and several environmental stress factors such as decrease in salinity and temperature (<13ºC) of sea water influenced the formation of WD 5,8,10,13 . Hepatic steatosis is accentuated in sea bream affected by WD and a polifactorial, metabolic-based pathology which causes high mortality when the water temperature drops below 11-13ºC 2,4 .…”
Section: Bi̇ri̇nci̇oğlu Aydoğan Avcimentioning
confidence: 99%